2005
DOI: 10.1590/s1413-70542005000500020
|View full text |Cite
|
Sign up to set email alerts
|

Determination of kinetic parameters of a lab-scale upflow anaerobic sludge blanket reator (uasb) removing organic loading from swine manure effluents

Abstract: The present work aimed at determining and evaluating the kinetic parameters from the UASB reactor treating swine manure effluent in a lab-scale experiment. The research was carried out in the Laboratory of Water Analysis at the Engineering Department (LAADEG) at the campus of Federal University of Lavras -UFLA. The system was assembled with an acidification and equalization tank (AET), an UASB reactor and an aerated facultative pond (AFP). The hydraulic retention time (HRT) adopted in the UASB reactor were: 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 1 publication
1
5
0
9
Order By: Relevance
“…With respect the error analyzed, also shown in ββ Table 1 -The models, the estimators and kinetics parameters UASB reactor. Henze et al (1997) Campos (2005), in an experiment that determined a K d of 0.0138 d -1 , value close to that determined in the UASB reactor in this study.…”
Section: Validation Of the Models And The Kinetic Parameterssupporting
confidence: 87%
See 2 more Smart Citations
“…With respect the error analyzed, also shown in ββ Table 1 -The models, the estimators and kinetics parameters UASB reactor. Henze et al (1997) Campos (2005), in an experiment that determined a K d of 0.0138 d -1 , value close to that determined in the UASB reactor in this study.…”
Section: Validation Of the Models And The Kinetic Parameterssupporting
confidence: 87%
“…The kinetic parameters were determined using the Monod kinetic model, described by Campos et al (2005) and Bhunia;Ghangrekar (2008), briefly deduced herein as follow: Inflow -outflow = Acumulation -Conversation μ Where: X r = concentration of biomass in the effluent (mg L -1 ); X: concentration of biomass of the effluent (mg L -1 ); Co =: the afluent substrate concentration (mg L -1 ); C = the substrate concentration in the effluent (mg L -1 ), : specific …”
Section: Modelling For Maximum Specific Growth Rate (µ Max ) and Satumentioning
confidence: 99%
See 1 more Smart Citation
“…The AET was operated at different flow rates, depending on the type and characteristics of the influent. Campos et al (2005a) worked on a laboratory scale with swine effluent and observed the accumulation of solids in the bottom of the AET caused by the excessive hydraulic retention time (HRT). This study also showed that the HRT caused an increase in the concentration of settling solids, which was repressed in the AET (Fig.4).…”
Section: Sedimentationmentioning
confidence: 99%
“…This enables the identification of operational factors (substrate, temperature, pH, among others) that affect kinetics, thereby contributing to the establishment of optimal operational conditions for the treatment process [8,9].…”
Section: Introductionmentioning
confidence: 99%